Ionising radiation risk disclosure: When should radiographers assume a duty to inform?. Issue 2 (May 2018) - Younger, C.W.E.; Douglas, C.; Warren-Forward, H.
Abstract: Introduction: Autonomy is a fundamental patient right for ethical practice, and informed consent is the mechanism by which health care professionals ensure this right has been respected. The ethical notion of informed consent has evolved alongside legal developments. Under Australian law, a provider who fails to disclose risk may be found to be in breach of a duty of disclosure, potentially facing legal consequences if the patient experiences harm that is attributable to an undisclosed risk. These consequences may include the common law tort of negligence. Ionising radiation, in the form of a medical imaging examination, has the potential to cause harm. However, stochastic effects cannot be attributable to a specific ionising radiation event. What then is the role of the Australian medical imaging service provider in disclosing ionising radiation risk? Methods: The ethical and legal principles of informed consent, and the duty of information provision to the patient are investigated. These general principles are then applied to the specific and unusual case of ionising radiation, and what responsibilities apply to the medical imaging provider. Finally, the legal, professional and ethical duties of the radiographer to disclose information to their patients are investigated. Results: Australian law is unclear as to whether a radiographer has a common law responsibility to disclose radiation risk. There is ambiguity as to whether stochastic ionising radiation risk could be considered a legal disclosure responsibility. Conclusion: While it is unlikely that not disclosing risk will have medicolegal consequences, doing so represents sound ethical practice. Highlights: Australian radiographer risk disclosure remains a matter for the undeveloped common law. In Australia, the duty to disclose is legislatively recommended for medical practitioners only. Non-disclosure of stochastic effect risk has an almost negligible medicolegal risk. Radiologists may delegate risk disclosure duties to other staff, including radiographers. For good practice, radiographers are encouraged to gain informed consent before any examination.